Discovery Health and the allied benefits saga : underestimating the power of social media? - Pitt, Leyland F., (SAGE Knowledge. Cases., 2018)
Discovery Health (Discovery) is a private healthcare funder in South Africa. In late 2011 and early 2012 it was in the midst of a crisis regarding the medical coverage it provided to allied professionals. The company decided to change the coverage, and the response of consumers and the general public was negative and significant. This crisis seemed to have taken on a life of its own via social media. The company responded to the growing storm on its website, on Facebook, and by regular tweets on the micro-blogging site Twitter. Yet the rumblings persisted, and seemed to be growing. How could Discovery deal with and resolve the issues? And perhaps most importantly of all, how could the firm ensure that there would not be repeat performances and similar crises in the future?